Manusia dalam Perspektif Al-Qur’an dan Psikologi - Asma, Fery Rahmawan (Al Ashriyyah, 2021)
Humans are the best creatures created by Allah SWT (ahsani taqwim). Allah honors it with various virtues as a basis for the process of becoming Allah's caliph on this earth. Therefore, humans must really realize who they are, what their essence is and what their role is in society that leads to their knowledge of the greatness of the Essence of Allah. Thus, this paper examines humans from a religious philosophical perspective around how the Qur'an views humans, the phases of their creation, the positive and negative sides of humans, as well as psychologists' views on humans and their growth and development.